Sosialisasi Strategi Penanganan dan Pencegahan Stunting - Fitri, Sri Lela; Jannah, Raudatul; Aulia, Lira Asmaul; Hatami, M. Yudi (Insan Kreasi Media, 2023)
Stunting is one of the most significant issues. The aim of the stunting service is to help the community understand and prevent stunting in children and pregnant women. The method used is to socialize strategies for preventing and treating stunting disease. In the process, socialization activities take place which are led by a moderator and the material is delivered by the community health center and nutritionists, so that participants can receive the material carefully and in a conducive manner. The process of preparing this socialization activity began with a light discussion with the local community about stunting, continuing at a task division meeting in preparing the socialization activity. After that, this socialization is expected to open people's insight regarding the dangers of stunting in children, the importance of maintaining children's health and growth and development and the importance of posyandu for children and pregnant women. Thus, socialization about stunting in Mumbul Sari Village has had a positive impact on community awareness, knowledge and behavior in efforts to prevent stunting. Continued steps and further support from the government and related parties are still needed to achieve greater stunting prevention goals in the future.